Fracture surfaces of the secondary A226 cast alloy with 0.9% Fe. (November 2019) - Kuchariková, Lenka; Mazur, Magdalena; Tillová, Eva; Chalupová, Mária; Závodská, Denisa; Vaško, Alan
Abstract: The fracture behaviours of Al-Si-Cu castings are very important due to their application for components for automotive and aerospace industry. Application such aluminium alloys is thanks to the excellent combination of their mechanical properties. Mechanical properties relate with microstructure. Today, an increasing amount of the aluminium, used for producing new aluminium alloy products, is coming from the recycled products. The recycled (secondary) aluminium cast alloys are containing more additional elements (especially higher amount of Fe) and are forming various second phases in microstructure. In general, a dimple type (transcrystalline ductile) fracture appears on the fracture surface of aluminium alloys, but the overall appearance of the fracture surface shows not only a violation of the matrix (α-phase), but also of the shape and size of eutectic Si and the second (intermetallic) phases especially Fe-rich phases. This paper describes changes of the fracture surfaces' character depending on the morphology and types of the second phases in the secondary A226 cast alloy with 0.9% of Fe. Since castings from those materials are commonly heat treated, the material was heat-treated and characteristics of the fracture surface and morphology of the second phases in microstructure were observed, too. Assessment was done by using a combination of different analytical techniques (scanning electron microscopy - upon black-white etching, deep etching, energy dispersive X-ray analysis and Backescattered electron images). Highlights: second phases in microstructure of recycled (secondary) aluminium cast alloys. the fracture surfaces' character depending on the morphology and types of the second phases parameters of heat treated – temp. 515 °C; water quenching at 60 °C and artificial aging at 170 °C with holding time of 16 h. the both phases (Fe and Cu-rich) have identical morphology on the deep etched samples as on the scratch. the Fe-rich phases in the skeleton like form and Cu-rich second phases does not have the negative impact as the platelets.